Pengaruh Store Atmosphere, Sales Promotion, dan Hedonic Shopping Motivation terhadap Impulsive Buying dimediasi oleh Positive Emotional Response pada Toko Ritel Sepatu Kulit Lokal: Toko XYZ - Agios Gerasimos Bisotwo Purnomo; Tarandhika Tantra (Masyarakat Ekonomi Syariah Bogor, 2024)
The fashion industry in globalization is on the rise. These changes have an impact on the way we produce and look fashion. Impulsive Buying such a problem that has an impact on consumers and business health. It was found that Store Atmosphere, Promotion, Hedonic Shopping, and Positive Emotion were the driving factors for the problem. The study aims to determine the effect of Store Atmosphere, Sales Promotion, Hedonic Shopping Motivation on Impulsive Buying in XYZ store as a leather shoe store mediated by Positive Emotional Response. This study is descriptive-causal with quantitative approach. The population in the study is Indonesian people who have shopped at XYZ store. The research sample was 414 with non-probability sampling technique. Data collection was conducted through questionnaires, analyzed quantitatively with SEM using of Smart-PLS. The results of the study stated that Hedonic Shopping has a positive and significant effect on Positive Emotional and Impulsive Buying same as Positive Emotional did. Positive Emotion successfully mediates the influence of Hedonic Shopping on Impulsive Buying. Store Atmosphere, and Sales Promotion had no influence on Impulsive Buying and Positive Emotion. Suggestions were given to XYZ store to maximizing quality control, store atmosphere, and interesting events in the store.